α9 Nicotinic Acetylcholine Receptor Promotes Tumor Proliferation and Suppresses Ferroptosis in Triple-Negative Breast Cancer - Xiaoli Feng; Yuxi Tian; Xijun Guo; Josh Haipeng Lei; Jiaqi Yu; Chenglong Zheng; Mingyue Chen; Ren-Bo Ding; Hang Fai Kwok; Sulan Luo; Jiaolin Bao (Biomolecules)
Breast cancer is a major global health burden with the highest incidence in women, and triple-negative breast cancer (TNBC) stands out as the most malignant subtype. Effective therapeutic targets are urgently needed to develop new therapies for TNBC. Nicotinic acetylcholine receptor is a ligand-gated ion channel receptor that is associated with the advancement of multiple cancers. Notably, α9 nicotinic acetylcholine receptor (α9 nAChR) is less investigated towards its role in cancer. This study sought to clarify the significance of α9 nAChR in TNBC. Firstly, our results uncovered that the expression of CHRNA9 was notably elevated in TNBC tissues and was associated with poor prognosis of TNBC patients. Further, our data indicated that overexpression of α9 nAChR facilitated the growth of TNBC cells, via mechanisms of simultaneously activating AKT-, ERK- and STAT3-mediated proliferation and negatively regulating ferroptosis through promoting SLC7A11/GSH/GPX4 and Keap1/Nrf2/HO1 signaling. Conversely, CHRNA9 knockdown would completely reverse all this signaling, ultimately inhibiting TNBC tumor growth both in vitro and in vivo. Finally, we reported a specific polypeptide antagonist of α9 nAChR, GeXIVA[1,2] and exerted good anti-tumor effects in tumor-bearing mice of TNBC, which indicated a great potential of GeXIVA[1,2] to be further studied as a novel targeted therapy for TNBC. This study provides a scientific basis for establishing α9 nAChR as a novel therapeutic target for TNBC, which is worthy of further development in the future.